2015
DOI: 10.14740/jmc2142w
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Inferior Hip Dislocation

Abstract: Inferior hip dislocation (luxatio erecta femoris) is the least common form of hip dislocation, and mostly occurs in children. This type of dislocation is extremely rare in adults, and there have been a total of 10 case reports in the literature. This current report presents a 55-year-old male patient who was treated with sedation analgesia and closed reduction in the emergency department with traumatic inferior hip dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…We reviewed the English-language literature search and found only five reported cases of inferior hip dislocation in adult patients (age >16 years). [3][4][5][6][7] Among them, our patient is the oldest case reported with uneventful reduction.…”
Section: Discussionmentioning
confidence: 79%
“…We reviewed the English-language literature search and found only five reported cases of inferior hip dislocation in adult patients (age >16 years). [3][4][5][6][7] Among them, our patient is the oldest case reported with uneventful reduction.…”
Section: Discussionmentioning
confidence: 79%
“…The hip is usually immobilized for 4 weeks followed by partial weight bearing. The results of the dislocation in most studies have been found good with good range of motion and no features of avascular necrosis in most reports [ 30 ].…”
Section: Discussionmentioning
confidence: 99%